The Effect of a Problem-Based Learning Model Incorporating the Bintang Ajaib manipulative on Student Learning Outcomes and Activities - Robisha Zarifa Ribaah; Firma Yudha; Moh Putra Rus Afandi; Akbar Maulana Ilman; Mochammad Husaini (Universitas Teknokrat Indonesia, 2026)
This study aims to determine the effect of implementing the Problem-Based Learning (PBL) model, supported by the Bintang Ajaib teaching aids, on student learning outcomes and activities related to sequences and series in 10th grade at SMA NU Genteng Banyuwangi. This study employs a quantitative, quasi-experimental design, specifically a Nonequivalent Pretest-Posttest Control Group Design. The research sample consisted of an experimental class using the PBL model supported by the Bintang Ajaib teaching aids and a control class using conventional instruction. Data collection techniques included observation, documentation, and pretest and posttest assessments. Data analysis utilized the Shapiro-Wilk normality test, homogeneity test, and Independent Samples t-Test using SPSS version 27.0. The results showed a significance value (Sig. 2-tailed) of 0.007 < 0.05, so H₀ was rejected, and H₁ was accepted. The average learning achievement of students in the experimental class was 85.90, higher than that of the control class (79.39). In addition, student activity in the experimental class increased because students were more engaged in discussing, solving problems, and understanding concepts through concrete, engaging teaching aids. Thus, the Problem-Based Learning model, supported by the Bintang Ajaib teaching aid, is an effective alternative to mathematics instruction that improves student learning outcomes and engagement.